Administrative guardianship and its applications in Jordanian law: An analytical study of the Decentralization Law No. 49 of 2015 - Al-Momani, Jameel Husam Mohammad (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to reveal the nature of administrative guardianship over decentralized bodies and their applications in Jordanian law through the analysis of the Decentralization Law No. (49) of 2015. The inductive approach was also used for legislative texts related to the issue of administrative guardianship, and accordingly the current study reviewed the legal nature of administrative guardianship in Jordanian law and its most prominent applications on decentralization councils, by analyzing the legal texts included in the Decentralization Law No. 16 of 2015.Results showed that guardianship The administrative law in the Jordanian law extends to include the same council and its members, while the decentralization law of 2015 did not include any guardianship over the work of the provincial councils and the reason for this is that the nature of the work carried out by that council is executive work, and therefore such works do not need the approval of the central authority, so it was not The 2015 Decentralization Law includes any provincial council decisions that need to be approved by the guardianship authority.
Keywords: administrative guardianship; decentralization; Jordanian legislation